1971
DOI: 10.1039/tf9716700110
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of proton and deuteron transfer reactions of 4-nitrophenylnitromethane with triethylamine and tri-n-butylamine in acetonitrile solvent

Abstract: The second-order rate constants for the proton and deuteron transfer reactions between 4-nitrophenylnitromethane and the organic bases triethylamine and tri-n-butylaniine have been determined at eight different temperatures between 0 and 35"C, using the stopped-flow technique. The four reactions are characterized by low enthalpies of activation and large negative entropies of activation. The isotope effects give values for (AD: -AH$) of 1.02 and 0.74 kcal mol-' and (AS," -AS;) of 1.2 and 0.9 cal mol-l K-l for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1971
1971
1994
1994

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…We found that this bimole-'~u t h o r to whom correspondence may be addressed. cular proton transfer reaction gave a dissociated product in MeCN to a large extent, contrary to earlier reports (2)(3)(4)(5). Therefore the applicability of the Benesi-Hildebrand method (6) has been carefully discussed, to explain why it gave incorrect results in previous papers, published by different authors ( 1 ) .…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…We found that this bimole-'~u t h o r to whom correspondence may be addressed. cular proton transfer reaction gave a dissociated product in MeCN to a large extent, contrary to earlier reports (2)(3)(4)(5). Therefore the applicability of the Benesi-Hildebrand method (6) has been carefully discussed, to explain why it gave incorrect results in previous papers, published by different authors ( 1 ) .…”
Section: Introductionmentioning
confidence: 89%
“…4.0]undec-7-ene (DBU) has already been examined in acetonitrile (MeCN) solvent (1). We found that this bimole-'~u t h o r to whom correspondence may be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction of 4-nitrophenylnitromethane with three phenyl substituted derivatives of 2-phenyl-l , 1,3,3-tetramethylguanidine: 2- (4'-chloropheny1)-1,1,3,3-tetramethylguanidine, (1 The equilibrium measurements gave a linear plot of a/A (a, the initial concentration of acid; A , the equilibrium absorbance of the reaction mixture) with l l b (b, initial concentration of base), a relation expected for products existing in the form of ion pairs (29). The relation of a/A against A l b , expected to be linear when the product is in the form of separate ions (29), shows a distinct upward curvature so that the form of product is certain and in agreement with previous measurements (1,29).…”
Section: Resultsmentioning
confidence: 98%
“…The relation of a/A against A l b , expected to be linear when the product is in the form of separate ions (29), shows a distinct upward curvature so that the form of product is certain and in agreement with previous measurements (1,29). A molecular extinction coefficient of the order of The value of the molecular extinction coefficient, about 2 x lo4 dm3 mol-' cm-', is in good agreement with values found in previous measurements for reactions with 4-NPNM as an acid (1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation